PRODUTIVIDADE DE CULTIVARES DE SORGO SAFRINHA SOB DIFERENTES COBERTURAS VEGETAIS DO SOLO. - CONCEIÇAO, Jessé Santarém; MARTINS, Murilo Basttistuzzi; ALVES, Bruno Lucas; DOS SANTOS, Mateus Amara (ANAIS DO ENIC, 2025)
-